Improving Students’ Ability in Memorizing Quran through Talqin, Tikrar, and Muraja'ah Method at Grade 4 of State Elementary School 2 Bataraguru - Karisma, Diana; Jusu, La; Basri, Basri (Universitas Pahlawan Tuanku Tambusai, 2025)
The challenges experienced by Grade IV students at SD Negeri 2 Bataraguru in memorizing the Qur'an—such as poor memory, forgetfulness, low motivation, and inaccuracies in pronouncing makhraj and tajwid—serve as the background for this study. This classroom action research aims to improve students’ Qur'an memorization skills through the application of talqin, tikrar, and muraja’ah techniques. The talqin method involves the teacher reciting Qur'anic verses for students to imitate, followed by tikrar, where students repeatedly echo the verses. Finally, muraja’ah encourages students to regularly review previously memorized verses to ensure long-term retention. The research was conducted in two cycles, using tests, documentation, and observation as instruments, with a total sampling technique involving all students in the class. The results show a significant improvement in students' memorization abilities, with the average score increasing from 67.96 in Cycle I to 83.12 in Cycle II, categorized as very good. These findings indicate that the implementation of talqin, tikrar, and muraja’ah techniques is effective in enhancing Al-Qur’an memorization among elementary school students.